ANALYSIS OF GUNUNG KIDUL REGENCY GOVERNMENT POLICIES IN ACHIEVING THE SUSTAINABLE DEVELOPMENT GOALS TARGET OF CLEAN WATER AND SANITATION FOR VILLAGES - Angga Misbahuddin (Ikatan Dosen Menulis, 2024)
This study analyzes the policies of the Gunung Kidul Regency Government in achieving the Sustainable Development Goals (SDGs) related to clean water and sanitation in villages. The main challenges faced include limited access to clean water and sanitation facilities, which impact the quality of life of the community. This research uses a qualitative descriptive method with secondary data obtained from various literature sources on policy evaluation, SDGs, and clean water and sanitation villages. The analysis indicates that sustainable development at the village level is crucial for improving the quality of life for current and future generations. The implementation of clean water and sanitation management policies in Gunung Kidul Regency has shown positive results, with significant improvements in access from 2017 to 2021. Key success factors include infrastructure enhancement, community education, water resource protection, and multi-sector collaboration. The PAMSIMAS program and sanitation infrastructure assistance have significantly contributed to improving access to clean water and sanitation. Community education and outreach have raised awareness of the importance of sanitation and hygiene, while water source protection policies help maintain the quality and sustainability of clean water. Collaboration between the government, NGOs, and the private sector strengthens policy implementation through the provision of funding, technology, and resources. Although these policies have been effective, future challenges will focus on maintenance, quality improvement, and facility sustainability, especially in the face of the climate crisis. Cross-sector collaboration and continuous education will remain key to achieving inclusive and sustainable development goals.